2024
DOI: 10.1590/1519-6984.249124
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical features of cutaneous leishmaniasis in Khyber Pakhtunkhwa, Pakistan

Abstract: Current cross-sectional study was carried out between September 2019 to January 2020 at the Department of Pathology, Mardan Medical Complex (MMC), Mardan, and District Headquarter Hospital North Waziristan, Khyber Pakhtunkhwa (KP), Pakistan. The objectives of the current study were to determine the prevalence of leishmaniasis and its associated risk factors in selected districts of KP province, Pakistan. Altogether, three hundred and seventy-four (n=374) leishmaniosis patients were included in the current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…Conceptually, cutaneous leishmaniasis can manifest as localized, disseminated, or diffuse and presents as papules that evolve into ulcers with granular bases and borders, either as single or multiple lesions. The localized form is usually ulcerated with one to twenty lesions (Machado, Prates, Machado, 2019) The characteristics of cutaneous lesions observed in the patients of this study corroborate with the literature, where the cutaneous form of ATL is the most common in Brazil, representing more than 90% of cases (Iqbal et al, 2024). The occurrence of ulcers with granular bases and borders, mainly in the lower limbs, reinforces the typical pattern of the disease in the region (Tirone et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Conceptually, cutaneous leishmaniasis can manifest as localized, disseminated, or diffuse and presents as papules that evolve into ulcers with granular bases and borders, either as single or multiple lesions. The localized form is usually ulcerated with one to twenty lesions (Machado, Prates, Machado, 2019) The characteristics of cutaneous lesions observed in the patients of this study corroborate with the literature, where the cutaneous form of ATL is the most common in Brazil, representing more than 90% of cases (Iqbal et al, 2024). The occurrence of ulcers with granular bases and borders, mainly in the lower limbs, reinforces the typical pattern of the disease in the region (Tirone et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…According to the current research findings, males were affected by cutaneous leishmaniasis more than females. This finding is supported by the opinions of some national and international experts [ 15 20 ]. A higher proportion of males were diagnosed with cutaneous leishmaniasis than females, which may be due to a combination of factors, such as greater exposure to the disease because men tend to work outdoors and are less likely to wear protective clothing, leading to a higher incidence of infected sand fly bites, or less frequent medical attention because women may have less access to health-care facilities.…”
Section: Discussionsupporting
confidence: 61%
“…Similarly, a study conducted including local and Afghan refugees in the Lower Dir district of KPK revealed 51% positivity [ 14 ], while there was 50.6% positivity in Baluchistan [ 6 ]. Another study in North Waziristan reported 53.7% positivity for cutaneous leishmaniasis [ 15 ]. Over the last several decades, this region has been politically unstable due to ongoing military operations against terrorists.…”
Section: Discussionmentioning
confidence: 99%